2017
DOI: 10.1002/ca.22903
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility assessment of shear wave elastography to lumbar back muscles

Abstract: Low back pain is often associated with tensional changes in the paraspinal muscles detected by palpatory procedures. Shear wave elastography (SWE), recently introduced, allows the stiffness of muscles to be assessed noninvasively. The aim of this work was to study the feasibility of using SWE on the three main lumbar back muscles (multifidus, longissimus, and iliocostalis) in vivo after analyzing their muscular architecture ex vivo. We determined the orientation of fibers in the multifidus, longissimus, and il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 34 publications
3
31
1
Order By: Relevance
“…In accordance with prior findings, ES exhibited significant greater stiffness than multifidus in all postures (Creze et al, ; Creze et al, ). Multifidus exhibited proportionally greater stiffness changes from procubitus to seated position.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In accordance with prior findings, ES exhibited significant greater stiffness than multifidus in all postures (Creze et al, ; Creze et al, ). Multifidus exhibited proportionally greater stiffness changes from procubitus to seated position.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the multifidus stiffness value, our findings are lower than those of previous studies using SWE and strain elastography (Chan et al, ; Moreau et al, ; Creze et al, ; Dieterich et al, ; Koppenhaver et al, ). Earlier reports found greater stiffness in ES resting than in our study (Kelly et al, ; Koppenhaver et al, ).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…In LPM, only shear wave sonoelastography (SWE) and strain sonoelastography have been used to date. The mean SM of the multifidus was 8.5 kPa and 5.4 kPa using SWE (Creze et al, ). Using strain elastography, Chan et al () found a mean Young's modulus of 36.4 kPa (corresponding to SM = 12 kPa).…”
Section: Discussionmentioning
confidence: 99%